Biochemical and functional characterization of the interaction between two receptor tyrosine kinases, ROR1 and MuSK - Summala, Katja (2019)
Receptor tyrosine kinase-like orphan receptor 1 (ROR1) is a closely related homolog to MuSK, Muscle-specific kinase. MuSK functions mainly in the muscle where it is active in the formation of neuromuscular junction (NMJ) by gathering acetylcholine receptors at the synaptic sites, although MuSK has been detected in other tissues as well. ROR1 is present in the brain during embryonic development, where it functions in neurite elongation, differentiation of neural cells and synapse formation. Even though ROR1 is mostly absent in adult tissues except in several types of cancer, it has also been detected in muscle, spleen and intermediate B-cell population called hematogones. We hypothesized that ROR1 and MuSK interact during the neuromuscular junction formation. The aim of this study was to characterize the properties of ROR1-MuSK interaction and show their endogenous expression in mouse skeletal muscle cell line C2C12 myotubes and neurons. Our results show that ROR1 can interact with MuSK and ROR1 is phosphorylated by MuSK when these receptors are overexpressed in 293T and Cos-7 cells, via co-immunoprecipitation and Western blot. We detected the endogenous expression of ROR1 in mouse skeletal muscle C2C12 cells with qPCR and co-immunoprecipitation. Since ROR1 was previously believed to only be expressed during embryonic development and in cancer, it became a target for cancer drug development. Our results show that ROR1 has a function in muscle cells, in the formation of the NMJ by interacting with MuSK. We also show that ROR1 is present in muscle tissue, which has clinical importance in the development of cancer treatments. Taken together, our studies provide novel information about ROR1 expression and function.